Kompetensi Anak Dalam Mengambil Keputusan Konsumsi serta Regulasi dan Pemberdayaan Konsumen Anak dalam Mengkonsumsi Makanan Jajanan - Triwijayati, Anna (Universitas Brawijaya, Indonesia, 2012)
Children consumer can take consumption decisions. Children consumers are unique because they have lack abilities and cognitive skills compared to older consumers. This study aims to describe the phenomenon of children ability to make decisions independently to buy snacks. ? What is known and taken into consideration and how we can build children consumer empowerment. The method used is phenomenology. Data obtained from interview with 10 informants of children and mothers. The results show thatchildren take decisions of consumption independently but not with full consideration. Reference factors which are teachers, parents, and product determine a quick evaluation or choice of alternative of snack product. Physical and psychological needs become the basis of quick evaluation of alternative of product and purchasing decisions by children consumers. This study also gives the concept of children consumer empowerment in order make decisions.